The efficacy of immune checkpoint inhibitors in advanced EGFR-Mutated non-small cell lung cancer after resistance to EGFR-TKIs: Real-World evidence from a multicenter retrospective study - Hu, Jia; Huang, Di; Wang, Yanrong; Li, Donghui; Yang, Xuejiao; Fu, Yan; Du, Nan; Zhao, Yan; Li, Xiaosong; Ma, Junxun; Hu, Yi (Frontiers in Immunology, 2022)
Background: The efficacy of immune checkpoint inhibitors (ICIs) in pretreated EGFR-mutated non-small cell lung cancer (NSCLC) patients is controversial. We conducted this multicenter retrospective study to examine the efficacy of ICIs in a real world setting. Patients and methods: We collected 116 consecutive NSCLC patients with sensitive EGFR mutations who received ICIs alone or in combination after failure to respond to EGFR tyrosine kinase inhibitors (EGFR-TKIs), and 99 patients were included for final analysis. The impacts of ICIs on the patients’ objective response rate (ORR), disease control rate (DCR), progression-free survival (PFS), and overall survival (OS) were assessed. The relationships between outcomes and clinical characteristics were analyzed. Results: The ORR in patients with target lesions was 31.25% (95% CI: 22.18-41.52), and the DCR in all patients was 65.66% (95% CI: 55.44-74.91). The overall median PFS was 5.0 months (95% CI: 3.0-6.6), and the median OS was 15.9 months (95% CI: 10.8-23.8). The outcomes were better in patients receiving combination therapy with ECOG scores of 0-1 and no more than 2 lines of prior therapy, with a median PFS of 7.4 months (95% CI: 3.0-13.3) and a median OS of 29.0 months (95% CI: 11.7-NE). Primary EGFR mutation type and treatment mode were found to have a notable impact on clinical outcomes. Both median PFS and OS in patients with EGFR L858R mutation were significantly shorter than those in patients with EGFR exon 19 deletion (19del) (PFS: 2.5 versus 6.7 months, HR: 1.80, log-rank P=0.011; OS: 9.8 versus 26.9 months, HR: 2.48, log-rank P=0.002). Patients receiving combination therapy had notably longer median PFS and OS than those receiving monotherapy (PFS: 5.2 versus 3.0 months, HR: 0.54, log-rank P=0.020; OS: 19.0 versus 7.4 months, HR: 0.46, log-rank P=0.009). Conclusions: Our study suggests that ICI-based combination therapy is a potential strategy for EGFR-mutated NSCLC patients after EGFR-TKI failure. The efficacy might differ according to EGFR subtypes.